2019
DOI: 10.3389/fnins.2018.01042
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Vestibular Inputs Affect Muscle Synergies Responsible for Body Extension and Stabilization in Sit-to-Stand Motion

Abstract: The sit-to-stand motion is a common movement in daily life and understanding the mechanism of the sit-to-stand motion is important. Our previous study shows that four muscle synergies can characterize the sit-to-stand motion, and they have specific roles, such as upper body flexion, rising from a chair, body extension, and posture stabilization. The time-varying weight of these synergies are changed to achieve adaptive movement. However, the relationship between sensory input and the activation of the muscle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Scholz et al also showed that how much sensory input can be used affects motion trajectory [9]. In addition, we previously clarified that muscle synergy in the sit-to-stand motion is changed due to disturbance of the visual or vestibular input [10]. In this study, we have clarified that visual input affects only the synergy that activates on the transitional period from sit-to-stand motion to posture control, and vestibular input affects the timing of the hip rise.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Scholz et al also showed that how much sensory input can be used affects motion trajectory [9]. In addition, we previously clarified that muscle synergy in the sit-to-stand motion is changed due to disturbance of the visual or vestibular input [10]. In this study, we have clarified that visual input affects only the synergy that activates on the transitional period from sit-to-stand motion to posture control, and vestibular input affects the timing of the hip rise.…”
Section: Introductionmentioning
confidence: 71%
“…For this research, the data of the control condition in our previous study [10] were used. In the measurement experiment, seven healthy people (six males and one female, aged 20-40 years, detailed age was not obtained) participated.…”
Section: Measurement Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the start, end, and duration time of temporal patterns were chosen because previous studies found that some post-stroke patients delayed or extended synergy activation, compared with other patients [26]. In addition, our previous study revealed that humans change the duration of muscle synergy to realize adaptive STS motion when their sensory information is impaired [32]. Then, the peak time was selected because our previous study found that the peak time affects STS strategies in healthy adults [24].…”
Section: E Muscle Synergy Featuresmentioning
confidence: 99%
“…Several studies have reported that the CNS regulates human motion and maintains balance by taking inputs from proprioceptors (Muscle Spindles (MS) and Golgi Tendon Organs (GTO)), tactile/somatosensory, visual, and vestibular systems [ 13 15 ]. Muscle feedback signals through proprioceptors suffer a delay in transmission to CNS [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%